CONSUMER PROTECTION AGAINST DEBTORS ON THE TRANSFER OF MORTGAGE RIGHTS VIA CESSIE - Dameria, Fiorella Angella; Djajaputra, Gunawan (Awang Long Law Review, 2024)
Disparities in financial capabilities in society have resulted in many credit agreements being entered into between consumers as debtors and banks as creditors or lenders, which are also accompanied by collateral in the form of mortgage rights which are used as collateral for payment of receivables by the debtor if he is unable to pay his debts to the creditor. The scope related to credit agreements is increasingly expanding when the model develops that credit agreements can be transferred to third parties through a cessie or receivable transfer agreement which of course poses risks for both creditors and debtors because in principle, when receivables are transferred to the cessie buyer, then the mortgage rights as collateral are also also transferred, including in terms of claim rights by new creditors. Therefore, this issue is interesting to discuss from the perspective of debtor protection as consumers of banking institutions, especially regarding the procedures and requirements that need to be understood regarding the transfer of mortgage collateral through a cessie or receivable transfer agreement. Apart from that, debtors also need to know what legal remedies can be submitted if the credit agreement or receivable transfer procedure causes losses for the debtor. In this research, the author uses a normative juridical research method using literature study and a legal approach. The results of the research show that based on the Consumer Protection Law and Financial Services Authority regulation, the Debtor as a consumer has the right to know clear and accurate information regarding the procedures and requirements of credit agreements including receivable transfer or cessie agreements and the legal consequences for the mortgage rights which he uses as collateral, including filing a complaint and/or legal remedies in litigation and non-litigation as long as he feels disadvantaged. The government needs to aggressively carry out outreach regarding all applicable regulations regarding credit agreements.